2007
DOI: 10.1007/s12087-007-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Buyer-Seller Relationships and the Economics of Information

Abstract: Section I In this paper, a theoretical framework is developed for the analysis of industrial buyer-seller relationships, using the concepts of search, experience and credence qualities, as known from Economics of Information theory. For this purpose, a dynamic perspective on this configuration is offered. By assuming a shift from experience qualities to search qualities in successive transactions, the evolution of the industrial buyer-seller relationship is explained. Section II The analysis indicates that Eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
9
1
Order By: Relevance
“…The significant effect of halal identity prestige on customer trust in this study supports Sichtmann (2007), who reported that brand reputation and brand prestige significantly impact customer trust. Another study showed that identity prestige not only affects customers’ perceived usefulness through customer trust (He et al , 2016) but also directly affects customer trust of halal restaurants.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The significant effect of halal identity prestige on customer trust in this study supports Sichtmann (2007), who reported that brand reputation and brand prestige significantly impact customer trust. Another study showed that identity prestige not only affects customers’ perceived usefulness through customer trust (He et al , 2016) but also directly affects customer trust of halal restaurants.…”
Section: Discussionsupporting
confidence: 86%
“…Concerning the relationship between halal company identity (halal identity similarity, halal identity distinctiveness and halal identity prestige) and customer trust, the result only confirms the roles of some aspects of a halal company identity. Although previous studies have indicated that company or brand identity affects customer trust (Doney and Cannon, 1997;He et al, 2012;Sichtmann, 2007;Keh and Xie, 2009;Walsh et al, 2009;Berens et al, 2005;Simoes et al, 2005), this study only showed that halal identity prestige positively affects customer trust, while halal identity similarity and halal identity distinctiveness do not successfully affect customer trust in the context of halal restaurants.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Sirdeshmukh et al (2002) define consumer trust as the expectation that a firm is dependable and will deliver on its promises. Sichtmann (2007) and Comegys et al, (2009) have found that trust in a firm positively affects purchase intentions. Chen ( 2008) also argues that potential consumers use online consumer reviews as one way to reduce risk and uncertainty in the purchase situation, as it provides prior service experience on which they can base their belief or trust that a firm will deliver quality service.…”
Section: Trust Degree Of Co-creation and Adoption Intentionmentioning
confidence: 97%